What is reparative justice? - Walker, Margaret Urban, 1948- (Aquinas lecture ;, 2010)
The idea of reparation, of amends owed for wrongs and wrongful harms, is ancient, universal, and a basic intuition of justice. Yet despite its ancient and distinguished lineage in Western philosophy, its familiar role in legal remedies for unjust losses and takings, and its increasing application to victims of political violence and repression, reparative justice has not received the wide consideration and sustained debate in contemporary thought that distributive and retributive justice have enjoyed. A fully developed conception of reparative justice would answer at least the following quest.